Muscone Ameliorates Ovariectomy-Induced Bone Loss and Receptor Activator of Nuclear Factor-κb Ligand-Induced Osteoclastogenesis by Suppressing TNF Receptor–Associated Factor 6-Mediated Signaling Pathways - Zhai, Xiao; Yan, Zijun; Zhao, Jian; Chen, Kai; Yang, Yilin; Cai, Mengxi; He, Chen; Huang, Chunyou; Li, Bo; Yang, Mingyuan; Zhou, Xiaoyi; Zhao, Yingchuan; et al. (Frontiers in Pharmacology, 2020)
Postmenopausal osteoporosis is caused by the deficiency of estrogen, which breaks bone homeostasis and induces levels of pro-inflammatory cytokines. Muscone is a potent anti-inflammatory agent, and is used to treat bone fracture in traditional Chinese medicine. However, its anti-osteoclastogenic effects remain unclear. For in vitro study, morphology tests of osteoclastogenesis were firstly performed. And then, factors in RANK-induced NF-κB and MAPK pathways were examined by RT-PCR and western blot, and the binding of TRAF6 to RANK was inspected by coimmunoprecipitation and immunofluorescence staining. For in vivo experiments, C57BL/6 ovariectomized　(OVX) mice were used for detection, including H&E staining, TRAP staining, and micro CT. As a result, muscone reduced OVX-induced bone loss in mice and osteoclast differentiation in vitro, by inhibiting TRAF6 binding to RANK, and then suppressed NF-κB and MAPK signaling pathways. The expression of the downstream biomarkers was finally inhibited, including NFATc1, CTR, TRAP, Cathepsin K, and MMP-9. The inflammatory factors, TNF-a and IL-6, were also reduced by muscone. Taken together, muscone inhibited the binding of TRAF6 to RANK induced by RANKL, thus blocking NF-kB and MAPK pathways, and down-regulating related gene expression. Finally, muscone inhibited osteoclastogenesis and osteoclast function by blocking RANK-TRAF6 binding, as well as downstream signaling pathways in vitro. Muscone also reduced ovariectomy-induced bone loss in vivo.